KEPUTUSAN PEMBELIAN VIRTUAL GOODS DITINJAU DARI KELOMPOK ACUAN, GAYA HIDUP DAN EVENT MARKETING (Studi pada players Mobile Legends: Bang Bang di Universitas Islam Batik Surakarta) - Yogi Ageng Wiratri; Ida Aryati; Sarsono Sarsono; Raisa Aribatul Hamidah (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this. study was to analyze the simultaneous and partial influence of the reference group, lifestyle and event marketing on the decision to purchase virtual goods on Mobile Legends: Bang Bang players at the Islamic Batik University Surakarta. This type of research is descriptive quantitative. The populationt is all consumers who purchase virtual goods at the Islamic Batik University Surakarta with an unknown amount. The sampling technique in this study was purposive proportional sampling. The sample is 100 studentstfrom the Islamic Batik University Surakarta. Data obtained from questionnaire. The data analysis technique used is multiple linear regression analysis. F test prove that the reference group, lifestyle and marketing events simultaneously influence the decision to purchase virtual goods on Mobile Legends: Bang Bang players at the Islamic Batik University Surakarta, where Fcount is 37,527 > Ftable is 2,70 with a significance value of 0,000 < 0,05. t test show that the reference group, lifestyle and event marketing have a positive and significant effect on the decision to purchase virtual goods on players of Mobile Legends: Bang Bang at the Islamic Batik University Surakarta. Keywords : Reference Group; Lifestyle; Event Marketing and Purchase Decision